The Necessity Test in Korea—Beef and its Progeny - Ortino, Federico; Bartels, Lorand (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2025)
This article revisits the World Trade Organization (WTO) Appellate Body’s landmark ruling in Korea—Measures Affecting Imports of Fresh, Chilled, and Frozen Beef, which gave the first authoritative definition of “necessity” under Article XX of the General Agreement on Tariffs and Trade and introduced the now known “weighing and balancing” test. The ruling balanced three factors—the importance of the policy objective, the measure’s contribution to that objective, and its trade restrictiveness—and has had a lasting influence not only on WTO jurisprudence but also on investment law. The article compares this approach to the proportionality analysis familiar in EU law, which distinguishes between causation, necessity, and strict proportionality. It shows how subsequent WTO panels and the Appellate Body have applied the necessity test with some ambiguity: sometimes treating the factors as a threshold assessment, sometimes combining them with the search for less trade-restrictive alternatives, and sometimes engaging in more explicit balancing. While WTO Members retain the right to set their own level of protection, there is emerging evidence that highly trade-restrictive measures are held to a higher standard of contribution, suggesting an evolution toward strict proportionality in practice. The article concludes that the necessity test remains open-ended but is developing into a more flexible and nuanced tool for balancing trade liberalization with regulatory autonomy.